Validation of Ultra Performance Liquid Chromatography-Tandem Mass Spectrometry Coupled with Electrospray Ionization Method for Quantitative Determination of Ornidazole in Solid Dispersion - Agrawal, Gopal P.; Maheshwari, Rajesh Kumar; Mishra, Pradeep (Current Pharmaceutical Analysis, 2020)
Background and Objective: The present study describes the UPLC-MS/MS method validation for the analysis of ornidazole in solid dispersion. Methods: The proposed UPLC-MS/MS method utilizes BEH Shield RP18 column (2.1 mm 100 mm, 1.7 μm) with a gradient programmed mobile phase composed of water and acetonitrile at a flow rate of 0.4 mL/min which varies with time program. Ornidazole was detected by UPLC-MS/MS with three proton adducts at m/z 82.04, 128.05 as daughter ions and 220.03 as a parent ion in Multiple Reaction Monitoring (MRM) operated in positive mode. Results: Adducts at m/z 128.05 was found to be the most stable and showed higher intensity was selected for quantification of ornidaozle in solid dispersion. In the method, validation linearity was determined at concentration range of 10-100ng/mL and a correlation coefficient was found (r2) ≥0.9994. The limit of detection and limit of quantification were found to be 1.5 and 4 ng/mL, respectively. Inter and Intra-day precision was found within 0.33 and 0.11% and accuracy within 100.08% and 100.04%. Conclusion: A sensitive and selective UPLC-MS/MS method had been validated for the analysis of ornidazole in solid dispersion. The proposed method of analysis of ornidazole in solid dispersion can be used in quality control laboratories.
Keywords: ESI